Fruit and vegetable intake and odds of pediatric migraine. Issue 5 (17th November 2019) - Ariyanfar, Shadi; Razeghi Jahromi, Soodeh; Rezaeimanesh, Nasim; Togha, Mansoureh; Ghorbani, Zeinab; Khadem, Ebrahim; Ghanaatgar, Milad; Noormohammadi, Morvarid; Torkan, Zahra
Abstract : Purpose: Diet is recognized as a possible potential factor in migraine pathogenesis. Limited evidence exists on the effect of diet on pediatric migraine, so this paper aims to investigate the association between fruit and vegetable consumption and odds of migraine in children. Design/methodology/approach: The authors conducted a case-control study in tertiary Sina hospital, Tehran, Iran. A hundred children with migraine as case group and 190 sex-matched healthy controls were included in this study. Definite diagnosis of migraine was based on 2018 international classification of headache disorder 3 (ICHD3) criteria. Demographic and anthropometric characteristics were collected. Common dietary intake of participants was obtained using a validated semi-quantitative food frequency questionnaire. Findings: Children in the migraine group had significantly higher BMI and age compared with the control group ( p -value = <0.01). After adjustment for age, gender, BMI and total energy intake, a significant association between higher intake of vegetables in second tertile (OR: 0.47; CI: 0.24-0.92), fruits in third tertile (OR: 0.31; CI:0.14-0.69) and fiber in fourth quartile (OR:0.28; CI:0.095-0.85) was obtained. Controlling for all confounders in Model 3, the odds of migraine, decreased by 50 per cent and 70 per cent as the consumption of vegetables and fruits increased, in the second tertile of vegetables ( p -value = 0.04) and the third tertile of fruits ( p -value = <0.01). Originality/value: The findings confirm a plausible protective role of dietary fruits and vegetables against the risk of migraine in children, which can be attributed to the probable effect of dietary fiber.